2018
DOI: 10.1080/12298093.2018.1538074
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ectomycorrhizal Colonization on Cesium Uptake by Pinus densiflora Seedlings

Abstract: Radionuclides were deposited at forest areas in eastern parts of Japan following the Fukushima Daiichi Nuclear Power Plant incident in March 2011. Ectomycorrhizal (EM) fungi have important effects on radiocaesium dynamics in forest ecosystems. We examined the effect of colonization by the EM fungus Astraeus hygrometricus on the uptake of cesium (Cs) and potassium (K) by Pinus densiflora seedlings. Pine seedlings exhibited enhanced growth after the EM formation due to the colonization by A. hygrometricus. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Mycorrhiza is an essential factor improving the mineral nutrition, growth, and development of host plants, which can significantly increase the effectiveness of plants in absorbing water and nutrients from the soil 43 , 44 . Sebastiana 45 demonstrated that the rate of Mycorrhizal infection caused different responses to changes in the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhiza is an essential factor improving the mineral nutrition, growth, and development of host plants, which can significantly increase the effectiveness of plants in absorbing water and nutrients from the soil 43 , 44 . Sebastiana 45 demonstrated that the rate of Mycorrhizal infection caused different responses to changes in the external environment.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing microbial load, respiration will increase 42,43 , inevitably leading to strong priming of SOC. However, this nding contradicts the hypothesis that adding logging residues will increase SOC content; thus, it has been proposed that microorganisms are negatively correlated with SOC compounds at a xed time point, while at a dynamic level, microorganisms are positively correlated with organic carbon compounds 44 . This proposition could explain why our hypothesis about the relationship between residue additions and SOC was not supported.…”
Section: Addition Of Logging Residues Can Increase Soil Carbon Contentmentioning
confidence: 75%
“…Generally, konara oak forms symbiotic associations with ectomycorrhizal species, whereas Japanese cedar forms associations with arbuscular mycorrhizal species. Incubation experiments on seedlings have suggested that the former fungal species enhance the solubilization of 137 Cs-fixing minerals and root uptake of 137 Cs to a greater degree than do the latter species 56 58 . However, not only variations in the impacts of the experimental conditions (e.g., the 137 Cs and K concentrations and their ratio in the soil or solution culture) on the results 58 60 , but also completely opposite results—that is, a decline in root uptake 61 —have been reported.…”
Section: Discussionmentioning
confidence: 99%